2008
DOI: 10.1016/j.juro.2008.03.105
|View full text |Cite
|
Sign up to set email alerts
|

Management of Urachal Remnants in Early Childhood

Abstract: A small urachal remnant, especially at birth, may be viewed as physiological. Urachal remnants in patients younger than 6 months are likely to resolve with nonoperative management. However, if symptoms persist or the urachal remnant fails to resolve after 6 months of age, it should be excised to prevent recurrent infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 9 publications
2
62
0
4
Order By: Relevance
“…Only 1 patient had recurrent symptoms, which were treated conservatively. Galati et al [7] retrospectively reviewed 23 patients treated for a UR, and found that overall 50% and in children less than 6 months of age 80% of URs resolved non-operatively. Lipskar et al [8] reviewed their experience in managing 15 children with URs.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 patient had recurrent symptoms, which were treated conservatively. Galati et al [7] retrospectively reviewed 23 patients treated for a UR, and found that overall 50% and in children less than 6 months of age 80% of URs resolved non-operatively. Lipskar et al [8] reviewed their experience in managing 15 children with URs.…”
Section: Discussionmentioning
confidence: 99%
“…Urachal anomalies can be described based on the extent of urachal patency as a patent urachus (entire tract patent), urachal cyst/alternating sinus, umbilical-urachus sinus (umbilical side patent), and vesico-urachal diverticulum (bladder side patent) occurring in 50%, 30%, 15%, and 3-5% of urachal abnormalities, respectively [6][7][8]. The persistence of the urachal lumen manifests in several clinical presentations, of which recurrent periumbilical discharge is the most common [9], following by abdominal mass.…”
Section: Introductionmentioning
confidence: 99%
“…Az urachus nyitva maradása az esetek harmadában az urogenitalis rendszer valamilyen egyéb fejlődési rendellenességével jár együtt (vesicoureteralis refl ux, hydronephrosis, ureteropelvic-junctio obstrukciója vagy ovariumcysta) [2].…”
unclassified
“…Az urachus nem teljes záródása -főleg a születéskor -még fi ziológiásnak tekinthető, és amennyiben nem okoz tüneteket, 6 hónapos életkor előtt nem igényel semmilyen beavatkozást [2], egyéves kor alatt is csak akkor javasolt sebészeti ellátása, ha a panaszok kiújulnak [3,4]. 16 éves kor alatt a visszatérő urológiai panaszok hátterében ugyanakkor 60%-ban az urachus fejlődési rendellenessége igazolható [5].…”
unclassified
See 1 more Smart Citation